DETERMINATION OF LAYER-CHARGE CHARACTERISTICS OF SMECTITES - Christidis G.E.; Eberl D.D. (My University, 2003)
A new method for calculation of layer charge and charge distribution of smectites is proposed. The method is based on comparisons between X-ray diffraction (XRD) patterns of K-saturated, ethylene glycol-solvated, oriented samples and calculated XRD patterns for three-component, mixed-layer systems. For the calculated patterns it is assumed that the measured patterns can be modeled as random interstratifications of fully expanding 17.1 A˚ layers, partially expanding 13.5 A˚ layers and non-expanding 9.98 A˚ layers. The technique was tested using 29 well characterized smectites. According to their XRD patterns, smectites were classified as group 1 (low-charge smectites) and group 2 (high-charge smectites). The boundary between the two groups is at a layer charge of -0.46 equivalents per half unit-cell. Low-charge smectites are dominated by 17.1 A˚ layers, whereas high-charge smectites contain only 20% fully expandable layers on average. Smectite properties and industrial applications may be dictated by the proportion of 17.1 A˚ layers present. Non-expanding layers may control the behavior of smectites during weathering, facilitating the formation of illite layers after subsequent cycles of wetting and drying. The precision of the method is better than 3.5% at a layer charge of -0.50; therefore the method should be useful for basic research and for industrial purposes.
Keywords: Charge Distribution; Expandable Layers; K-saturation; Layer Charge; LayerCharge Program; Profile Modeling; Smectite; X-ray Diffraction